Types Of Assimilation Of Borrowed Words From French To English Language: Jenis Asimilasi Kata Pinjam Dari Bahasa Prancis Ke Bahasa Inggris - Safarova Khurshida Salimovna (Academia Open, 2022)
More than half of the etymological structure of modern English consists of borrowed words, the first of which are words borrowed from French. Although the fact of the influence of French on the vocabulary of English has been repeatedly noted, the nature of this influence has not been sufficiently studied.